Inovasi Pelayanan Perputakaan di Taman Bacaan Masyarakat Lingkaran Cahaya selama Pandemi Covid-19 - Rifki Rizkia Malik; Sukaesih Sukaesih; Evi Nursanti Rukmana; Samson CMS (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2020)
The Covid-19 pandemic has had a tremendous impact on all sectors of society, including information institutions such as libraries and Community Reading Park which have been affected. Community Reading Park has also innovated to survive during a pandemic by developing collections, reference services, and circulation services at Community Reading Park The purpose of this study was to determine the innovation of the Circle of Light Community Reading Park during the Covid-19 pandemic. This study used a descriptive qualitative research method, in which the researcher conducted interviews and observations on the managers of the Circle of Light Community Reading Park. The innovation at Community Reading Park involves several aspects and services such as management, collection development, and services such as reference services and circulation services. This innovation is expected to attract people to carry out the function of Community Reading Park to increase reading interest during the Covid-19 pandemic.